2015
DOI: 10.1111/tri.12582
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-induced thrombotic microangiopathy after renal transplant successfully treated with eculizumab: case report and review of the literature

Abstract: De novo thrombotic microangiopathy (TMA) after renal transplant is rare. Cytomegalovirus (CMV)-related posttransplant TMA has only been reported in 6 cases. We report an unusual case of a 75-year old woman who developed de novo TMA in association with CMV viremia. The recurrence of TMA with CMV viremia, resolution with treatment for CMV and the lack of correlation with a calcineurin inhibitor (CNI) in our case supports CMV as the cause of the TMA. What is unique is that the use of eculizumab without plasmapher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 23 publications
(17 reference statements)
0
25
0
Order By: Relevance
“…Moreover, a virus associated complement-mediated destruction of endothelial cells might be involved because CMV has been reported to cause direct activation of the classical pathway and TA-TMA is a disease closely related with abnormalities of the complement system. [3,4,16] Serum LDH concentration > 500U/L was found to be an early marker for TA-TMA occurrence, and it elevated at a median of 6 days before TA-TMA diagnosis. This finding agreed to recent literatures that LDH could be an early marker of TA-TMA, and could be included in a noninvasive laboratory diagnostic panel for the early detection and prognosis of TA-TMA.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a virus associated complement-mediated destruction of endothelial cells might be involved because CMV has been reported to cause direct activation of the classical pathway and TA-TMA is a disease closely related with abnormalities of the complement system. [3,4,16] Serum LDH concentration > 500U/L was found to be an early marker for TA-TMA occurrence, and it elevated at a median of 6 days before TA-TMA diagnosis. This finding agreed to recent literatures that LDH could be an early marker of TA-TMA, and could be included in a noninvasive laboratory diagnostic panel for the early detection and prognosis of TA-TMA.…”
Section: Discussionmentioning
confidence: 97%
“… CMV No evidence. Case report of de novo TMA after kidney transplant in the context of CMV infection, and recurrence of TMA with recurrence of CMV viraemia in the absence of CNI; successfully treated with valganciclovir and eculizumab [ 163 ]. No evidence.…”
Section: Evidence For the Role Of Complement In The Tmasmentioning
confidence: 99%
“…Eculizumab, a monoclonal antibody which prevents the production of membrane attack complex (MAC) by inhibiting conversion of C5 to C5a and C5b, has been successfully tried in the treatment of TMA secondary to calcineurin inhibitor and cytomegalovirus (CMV). Discontinuation of causative agents and early initiation of eculizumab therapy protects against further complement mediated host cell damage and also provides ample time for the treatment of infections [66, 67]. Recently, a retrospective study conducted by Arai et al demonstrated that serum levels of neutrophil extracellular traps (NETs) were significantly elevated when compared to the pretransplantation level especially in patients developing TMA following HSCT.…”
Section: Pathophysiology Of Acute Kidney Injury In Hsctmentioning
confidence: 99%